2013
DOI: 10.1007/s11746-013-2375-0
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerizable Synthons from Glycerol Derivatives

Abstract: Photopolymerizable monomers based on monoglycerides were prepared by a convenient two‐step procedure. The first one consists of the synthesis of highly pure monoglycerides by an organocatalyzed solvent‐free route. This process was carried out by condensation of bio‐sourced carboxylic acids (i.e. butyric, decanoic, undecylenic or stearic acids) with glycerol carbonate or glycidol in the presence of a quaternary ammonium salt as a catalyst. The obtained bio‐based monoglycerides were modified in the second step b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…By contrast with the synthesis pathway based on glycidol, the thermal condensation of glycerol carbonate with fatty acids is not well described in the literature. Previously run classical heating experiments showed that the reaction between glycidol and decanoic acid leads to better yield in shorter time than the reaction starting from glycerol carbonate and decanoic acid .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By contrast with the synthesis pathway based on glycidol, the thermal condensation of glycerol carbonate with fatty acids is not well described in the literature. Previously run classical heating experiments showed that the reaction between glycidol and decanoic acid leads to better yield in shorter time than the reaction starting from glycerol carbonate and decanoic acid .…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, conventional heating was performed . The best conditions were as follow: 24 h, 0.5 mol% of TBAI as catalyst and a molar ratio of carboxylic acid/glycerol carbonate of 1/2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Classically, the synthetic approach is based on the functionalization of bio-sourced molecules by the grafting of glycidyl ether groups. In this context and in our ongoing studies on the chemical modification of bio-based building blocks for material applications (Mhanna et al, 2014;Bigot et al, 2016;François et al, 2016), we report herein on the synthesis and crystal structure of the diglycidyl ether of eugenol (DGE-Eu), prepared from eugenol in a three-step synthesis (Qin et al, 2014).…”
Section: Chemical Contextmentioning
confidence: 99%